Correlation of Face Washing, Mask Use, and Acne Incidence During COVID-19 Among Gunadarma University Students - Warni Zulhija Putri; Fifinela Raissa; Wahyunia Septiana; Endang Rahmawati (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Prevention of COVID-19, in addition to washing hands and keeping distance, can be achieved by using masks regularly. The use of masks in the long term can cause acne vulgaris. Acne vulgaris is a chronic inflammatory condition in the pilosebaceous follicle. Acne vulgaris often occurs in adolescents and young adults. Housekeeping face aims to reduce bacteria, dirt, or microorganisms from the skin's surface by reducing sebum and impurities without removing the lipid barrier in the face. This study aims to understand the relationship between the habit of washing the face and using masks during the COVID-19 pandemic and the incidence of acne vulgaris in students at Gunadarma University, Depok. This type of research is an analytic observational cross-sectional design; the primary data is collected through questionnaires. The sample of this research is the students of the faculty of medicine at Gunadarma University. The sample size is as many as 64, and the sampling technique is simple random sampling. The data were analyzed using the SPSS program and tested using a multivariate logistic regression test. Statistical tests between the facial washing habits and acne vulgaris show a p-value = 0.948. This study shows no relationship between facial washing habits and acne vulgaris. The statistical test results between mask use and acne vulgaris show a p-value = 0.017. This study shows the presence of meaningful relationships between the use of the mask and acne vulgaris (OR = 3.992). The statistical test results of the type of mask with acne vulgaris p value> 0.05. This study shows no relationship between the kind of mask and the incidence of acne vulgaris. This study shows no relationship between facial washing habits and acne vulgaris. Still, there is a relationship between the use of masks and acne vulgaris, and there is no relationship between the type of mask and the incidence of acne vulgaris.